2006
DOI: 10.1097/01.qco.0000244049.15888.b9
|View full text |Cite
|
Sign up to set email alerts
|

American histoplasmosis in developing countries with a special focus on patients with HIV: diagnosis, treatment, and prognosis

Abstract: Direct examination of May-Grünwald-Giemsa-stained smears or tissues in suspected histoplasmosis is a simple means of confirming the diagnosis in resource-poor settings. Studies of prognostic factors should further refine indication criteria to guide first-line treatment choice between amphotericin B and itraconazole. The association of tuberculosis and histoplasmosis is frequent in HIV patients and presents diagnostic and therapeutic challenges that may be difficult to resolve in resource-poor settings. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
4
12

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(134 citation statements)
references
References 48 publications
6
112
4
12
Order By: Relevance
“…This finding agrees with the pattern of AIDS distribution in the Colombian population (36). Such a tendency has been reported in other series as well (2,3,7,(17)(18)(19)23).…”
Section: Diagnostic Methodssupporting
confidence: 83%
“…This finding agrees with the pattern of AIDS distribution in the Colombian population (36). Such a tendency has been reported in other series as well (2,3,7,(17)(18)(19)23).…”
Section: Diagnostic Methodssupporting
confidence: 83%
“…6 In the present study, after adjusting for CD4 cell counts, we found no significant difference in LDH levels between persons with tuberculosis and those Ferritin concentration has also been described as an indicator for the diagnosis of severe disseminated histoplasmosis. 25 However, because of a large number of missing values, this variable was not selected for multivariate analysis.…”
Section: Discussionmentioning
confidence: 45%
“…Rapid and sensitive antigenic detection techniques are not available in most countries. 6 The non-specific nature of the clinical, biologic, histologic, and radiologic findings for these two diseases makes differential diagnosis of histoplasmosis difficult in disease-endemic areas. Thus, numerous publications report cases of histoplasmosis mimicking tuberculosis, most often because of the absence of diagnostic facilities or because a diagnosis of histoplasmosis was not considered.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important to improve the description of the presentation of these pathologies and to develop better diagnostic tools to aid the therapeutic decisions of the clinicians. 6 In the meantime, a better knowledge of what causes AIDS in the region is precious because we strongly suspect histoplasmosis is a major but unrecognized cause of numerous deaths in and around the Amazon.…”
mentioning
confidence: 99%